Sintomas de impacto nutricional em indivíduos com câncer de cabeça e pescoço - Rosario, Thainá Cezini do (2024)
Introduction: Head and neck cancer (HNC) affects areas directly related to the digestive tract, leading to inadequate food intake and is consistently associated with symptoms that impact nutritional status (SIN). These symptoms exacerbate the reduction in food consumption, which affects nutritional status. Objective: To analyze the severity of SIN and the interference in oral intake on the nutritional status of pre-treatment HNC patients at a reference oncology center in Greater Vitória, ES, Brazil. Method: This is a study with HNC patients from a reference oncology hospital in the metropolitan region of Vitória. A questionnaire was administered, including sociodemographic, clinical, lifestyle, and dietary change variables. Anthropometric evaluation was performed, nutritional risk screening using NRS-2002, and SIN screening using the Head and Neck Patient Symptom Checklist (HNSC). Statistical analysis was conducted using R software (4.3.1) for Windows with a significance level of 5%. Results: A total of 132 individuals participated in the study. Multiple linear regression showed that cancer located in the larynx (p=0.031) was associated with an estimated reduction of 6.67 points in the SIN score compared to oral cavity location. Regarding smoking, former smokers (p=0.019) had an estimated reduction of 5.87 points in the SIN score compared to smokers, and those at nutritional risk (p=0.009) had an estimated increase of 6.15 points in the total SIN score compared to those not at nutritional risk. In nutritional status, it was observed that for every 1-point increase in the SIN interference severity score, there was an estimated reduction of 3.3 kg/m² in BMI and 3.0 cm in calf circumference (CC). Conclusion: Tumor location, smoking, and the presence of nutritional risk influence the quantity and severity of SIN. As the severity score for SIN interference with oral intake increases, there is a reduction in both BMI and CC, suggesting nutritional depletion. Strategies to improve nutritional status and control smoking are important for reducing symptoms and improving the quality of life of these patients.